Manuscript Transcription by Crowdsourcing: Transcribe Bentham - Moyle, Martin; Tonra, Justin; Wallace, Valerie (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2011)
Transcribe Bentham is testing the feasibility of outsourcing the work of manuscript transcription to members of the public. UCL Library Services holds 60,000 folios of manuscripts of the philosopher and jurist Jeremy Bentham (1748–1832). Transcribe Bentham will digitise 12,500 Bentham folios, and, through a wiki-based interface, allow volunteer transcribers to take temporary ownership of manuscript images and to create TEI-encoded transcription text for final approval by UCL experts. Approved transcripts will be stored and preserved, with the manuscript images, in UCL’s public Digital Collections repository. The project makes innovative use of traditional library material. It will stimulate public engagement with UCL’s scholarly archive collections and the challenges of palaeography and manuscript transcription; it will raise the profile of the work and thought of Jeremy Bentham; and it will create new digital resources for future use by professional researchers. Towards the end of the project, the transcription tool will be made available to other projects and services. This paper is based on a presentation given by the lead author at LIBER’s 39th Annual General Conference in Aarhus, Denmark, 2010.